2007
DOI: 10.2325/jbcs.14.260
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between FDG uptake in PET scans and biological behavior in breast cancer

Abstract: Mitotic count and Ki67 reflect cellular aggressiveness. These parameters were strongly correlated with tracer uptake. Thus our data suggested that the biological behavior of breast cancer is reflected in the variation of FDG uptake by the tumor. However, whether FDG uptake is a true prognostic and predictive factor remains to be confirmed in larger studies over an extended period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
4
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 16 publications
6
54
4
2
Order By: Relevance
“…Other previous studies are consistent with our result [14,16,21,32]. It has been reported that SUVmax of breast cancer shows a linear relationship in T1-T3 tumors and correlates with tumor size.…”
Section: Discussionsupporting
confidence: 94%
“…Other previous studies are consistent with our result [14,16,21,32]. It has been reported that SUVmax of breast cancer shows a linear relationship in T1-T3 tumors and correlates with tumor size.…”
Section: Discussionsupporting
confidence: 94%
“…Akin to others [4,6,8,10,34], our study revealed that primary malignant lesions with higher histopathologic grade and expression of Ki-67 showed significantly higher SUVmax (4.3 vs. 7.5 vs. 9.3; 4.6 vs. 8.7, respectively p < 0.001).…”
Section: Discussionmentioning
confidence: 72%
“…Most of the previous studies mainly assessed the correlation between each histopathologic factor and SUVmax [5][6][7][8][9][10][11][12]. Garcia et al [13] reported that semiquantitative parameters of F-18 FDG PET/CT showed statistically significant differences among the molecular subtypes according to the recommendations of St. Gallen consensus meeting 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The initial role of 18 FDG PET was in the differentiation between benign and malignant lesions, especially in indeterminate solitary pulmonary nodules (Lowe et al, 1998) with further exploration into grading and prognosis assessment of various tumours (Dimitrakopoulou-Strauss et al, 2001; Shimoda et al, 2007). Standardised uptake values have been shown to be reliable in differentiating between benign and malignant lesions in a number of situations, but in others visual analysis has been reported to be equivalent (Lowe et al, 1994).…”
Section: Clinical Applications Tissue Differentiation and Tumour Gradingmentioning
confidence: 99%
“…There is less evidence on the use of PET to determine grade of malignancy, with few dynamic studies reported. However, there is some evidence that 18 FDG PET correlates with tumour grade and infers prognosis in some tumour types, examples having been reported in bone, breast and brain tumours, among others (DimitrakopoulouStrauss et al, 2001;Borbely et al, 2006;Shimoda et al, 2007).…”
Section: Clinical Applications Tissue Differentiation and Tumour Gradingmentioning
confidence: 99%